Utilization The Combination of Taro (Colocasia Esculenta L. Schott) Leaves Flour and Soybean Flour in Artificial Feed on The Growth Weight of Carp Fish (Osphronemus Gourami L.) - Sefni, Sefni; Efrizal, Efrizal; Rahayu, Resti (Metamorfosa: Journal of Biological Sciences, 2019)
Research on utilization the combination of taro leaves flour ( Colocasia esculenta L. Schott) and soybean flour in artificial feed on the growth weight of carp fish ( Osphronemus gourami L.) was conducted from February to April 2016. The aim of this research was to determine the percentage of utilization the combination of taro leaves four and soybean flour in artificial feed on the growth weight of carp fish. This research uses a completely randomized design (CRD) with 4 treatments and 3 replications. The treatment in this research was a combination of taro leaves flour in artificial feed about 0%, 5%, 10% and 15%. The results showed that the combination of taro leaves flour ( Colocasia esculenta L. Schott) about (0, 5, 10 and 15%) with soybean flour in artificial feed formulation having the same effect (P>0,05) on the growth weight of carp fish.